Socioeconomic and Demographic Characteristics of Children Under Five Years of Age Suffering from Stunting in Magelang Regency, Indonesia - Sri Rum Giyarsih; Ratih Fitria Putri; Maulana Malik Sebdo Aji; Yuyun Arining Jayanti; Fauzi Darmawan; Darto Wahidin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
This study is set out to examine the socioeconomic and demographic characteristics of stunted children under five years of age in Magelang Regency, Central Java Province. Indonesia. It used questionnaire surveys (structured interviews) to collect data on 266 heads of households with stunted children under-five that had been selected using a tiered sampling method, then analyzed the data in the SPPS program. Also, in-depth interviews were conducted with informants from these households and staff of community health center, Health Office, Social Office, and Regional Development Planning Agency (BAPPEDA), and the resulting data were processed and analyzed through the stages of data reduction, data presentation, conclusion withdrawal, and verification. The quantitative data were tested for validity using the statistical procedures provided in the SPSS program, while the qualitative data were examined for their reliability by the triangulation method. The results showed that the majority of stunted children under-five in the regency had normal birth weight and length, received a complete series of immunization, and were breastfed. Furthermore, about one-third of the mothers were employed, showing that many of the families observed are less stable economically. This study also found that parents still lacked the knowledge to recognize stunting in their children, about 80 percent of which did not realize that their children experienced impaired growth and development. Another finding is that government programs have reached 50 percent of families with stunted children under-five.